On thermosolutal convection in presence of compressible fluid with fine dust - Singh, Mahinder; Gupta, R.K. (Zielona Góra: Uniwersytet Zielonogórski)
A layer of a Rivlin-Ericksen elastico-viscous fluid heated and soluted from below in the presence of compressibility and suspended particles (fine dust) effect is considered. For stationary convection, the Rivlin-Ericksen, elastico-viscous fluid behaves like a Newtonian fluid. The oscillatory modes are introduced due to the presence of a stable solute gradient, suspended particles destabilize the system whereas the stable solute gradient has a stabilizing effect on the system and the effect of compressibility is to postpone the onset of thermosolutal convection. The stable solute gradient and compressibility postpone the onset of convection, whereas the suspended particles hasten the onset of convection. The stable solute gradient introduces oscillatory modes in the systems which were non-existent in its absence.
Keywords: Rivlin-Ericksen elastico-viscous fluids; compressible dust; fine dust